Coxiella burnetii Nine Mile phase I primary infection derived protective immunity against C. burnetii reinfection in mice depends on both B and T cells, but T cells play a critical role - Alam, Shawkat; Kumaresan, Venkatesh; Palanisamy, Rajesh; Zhang, Yan; Seshu, Janakiram; Xiong, Na; Zhang, Guoquan (Frontiers in Immunology, 2024)
Coxiella burnetii is an obligate intracellular Gram-negative bacterium that causes acute and chronic Q fever in humans. Acute Q fever is usually a flu-like, self-limiting or treatable illness, but some infections can turn into a severe and sometimes fatal chronic disease. There is currently no FDA-approved vaccine available for the prevention of human Q fever in the US, development of a safe and effective vaccine for the prevention of human Q fever remains an important goal for public health. However, there is a fundamental gap in knowledge regarding the mechanism of protective immunity against C. burnetii infection. To understand the mechanism of C. burnetii infection induced protective immunity, we examined if C. burnetii Nine Mile phase I (NMI) infection induces protection against C. burnetii reinfection in mice. Our results indicate that NMIinfected mice conferred significant protection against C. burnetii reinfection. We also found that NMI infection derived protection did not depend on the routes of infection and antibodies are required for NMI infection derived protection. In addition, NMI infection elicited a comparable level of protection in Wild type, CD4 + T cell deficient, and CD8 + T cell deficient mice, partial protection in B cell deficient mice but no protection in T cell deficient mice. These results suggest that both B cells and T cells are required for NMI-infection derived protection, but T cells may play a critical role. Therefore, the new generation vaccine for the prevention of human Q fever should be focused on boosting both humoral and T cell immune responses.